Positive response to intravitreal ranibizumab in the treatment of choroidal neovascularization secondary to punctate inner choroidopathy. - Menezo, V; Cuthbertson, F; Downes, S (2010)
PURPOSE: The purpose of the study was to report the use of ranibizumab in choroidal neovascularization secondary to punctate inner choroidopathy. METHODS: This was a retrospective case series. Clinical notes of 10 patients with choroidal neovascularization secondary to punctate inner choroidopathy were reviewed (mean age, 40.7 years, age range, 25-58 years). RESULTS: Previous therapies included photodynamic therapy, posterior sub-Tenon's triamcinolone, oral prednisolone, and intravitreal triamcinolone. Ten eyes in 10 patients underwent a mean of 1.9 ± 1.3 (± standard deviation) injections of antivascular endothelial growth factor (range, 1-5). All 10 patients had a follow-up review of at least 6 months (median, 12.5 ± 9.2 standard deviation; range, 6-34 months). Nine eyes either maintained or improved vision by at least 1 line on the logarithmic of the minimal angle of resolution calculated equivalent chart at least 6 months after the start of treatment with antivascular endothelial growth factor therapy. No ocular or systemic complications were observed. CONCLUSION: The role of ranibizumab in choroidal neovascularization in association with punctate inner choroidopathy has been shown to be beneficial in this small group in whom improvement or stabilization of vision was observed in 9 of 10 eyes. Recurrent choroidal neovascularization can occur in these patients, and additional injections of ranibizumab appear to be safe and efficacious.